A new family with paroxysmal exercise induced dystonia and migraine: a clinical and genetic study. Issue 5 (1st May 2000) - Münchau, A; Valente, E M; Shahidi, G A; Eunson, L H; Hanna, M G; Quinn, N P; Schapira, A H V; Wood, N W; Bhatia, K P
Abstract : OBJECTIVE: To characterise the phenotype of a family with paroxysmal exercise induced dystonia (PED) and migraine and establish whether it is linked to the paroxysmal non-kinesigenic dyskinesia (PNKD) locus on chromosome 2q33–35, the familial hemiplegic migraine (FHM) locus on chromosome 19p, or the familial infantile convulsions and paroxysmal choreoathetosis (ICCA syndrome) locus on chromosome 16. METHODS: A family, comprising 30 members, was investigated. Fourteen family members in two generations including three spouses were examined. Haplotypes were reconstructed for all the available family members by typing several microsatellite markers spanning the PNKD, FHM, and ICCA loci. Additionally, the four exons containing the known FHM mutations were sequenced. RESULTS: Of 14 members examined four were definitely affected and one member was affected by history. The transmission pattern in this family was autosomal dominant with reduced penetrance. Mean age of onset in affected members was 12 (range 9–15 years). Male to female ratio was 3:1. Attacks of PED in affected members were predominantly dystonic and lasted between 15 and 30 minutes. They were consistently precipitated by walking but could also occur after other exercise. Generalisation did not occur. Three of the affected members in the family also had migraine without aura. Linkage of the disease to the PNKD, FHM, or ICCA loci was excluded as no common haplotype was shared by all the affected members for each locus. In addition, direct DNA sequential analysis of the FHM gene (CACNL1A4) ruled out all known FHM point mutations. CONCLUSIONS: This family presented with the classic phenotype of PED and is not linked to the PNKD, FHM, or ICCA loci. A new gene, possibly coding for an ion channel, is likely to be the underlying cause of the disease.